Effect of Different Enriched Crickets (Gryllus sigilatus) on Growth and Pigmentation of Asian Arowana (Scleropages formosus) Var. Super Red - Sukarman Sukarman; Rendy Ginanjar; Mochammad Zamroni; Idil Ardi; Ahmad Musa; Melta Rini Fahmi; Agus Priyadi; Muhamad Yamin (Bogor Agricultural University, Indonesia, 2023)
This study aimed to evaluate the effect of crickets enriched with a source of carotenoids on fish’s growth, colour, and total carotenoid content in juvenile Asian Arowana (Scleropages formosus). Six juveniles were fed with different enriched crickets (G. sigilatus) based on the following treatments: (A) Crickets fed with fish feed without enrichment, (B) Crickets fed with fish feed containing 500 ppm of synthetic astaxanthin, and (C) Crickets fed with a combination of 50% fish feed, 48% sand crab meal and 2% marigold petal meal. The results of the study revealed that The weight gain (WG), specific growth rate (SGR), feed efficiency (FE), length gain (LG), and survival rate (SR) for treatment A were 110 g, 1.16% head/day, 45.79%, 10.98 cm, and 100% respectively. There was also no significant difference (P>0.05) with the other treatments. However, treatment B had a positive effect on the redness (a*) of the Arowana tail with a value of 9.52, and treatment C increased the yellowness (b*) of the Arowana body with a value of 2.77 (P<0.05), which was different to the other treatments. There were no differences between any of the treatments concerning the effects on lightness (L*), chromaticity (C*), and hue (H*) on either the body or the tail. The astaxanthin enrichment produced the highest carotenoid content (P<0.05) with a value of 45.09 µg/g. Enriching crickets with astaxanthin influence colour and carotenoid content but not the growth of the Asian Arowana fish.